2012
DOI: 10.1371/journal.pone.0031483
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of the Pollen Allergen Bet v 1.0101 Enhances the Presentation of Bet v 1-Derived Peptides by HLA-DR on Human Dendritic Cells

Abstract: Nitration of pollen derived allergens can occur by NO2 and ozone in polluted air and it has already been shown that nitrated major birch (Betula verrucosa) pollen allergen Bet v 1.0101 (Bet v 1) exhibits an increased potency to trigger an immune response. However, the mechanisms by which nitration might contribute to the induction of allergy are still unknown. In this study, we assessed the effect of chemically induced nitration of Bet v 1 on the generation of HLA-DR associated peptides. Human dendritic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 44 publications
(45 reference statements)
3
65
0
Order By: Relevance
“…In this regard, nitrated α-synuclein is detected in cervical lymph nodes of mice when treated with MPTP, but not in healthy mice (Benner et al 2008). It is noteworthy that nitration of proteins not only enhances antigen presentation by human dendritic cells, but also promotes a strong activation and proliferation of specific Tcell clones (Karle et al 2012). Consistent with these findings, the adoptive transfer of T-cells obtained from mice immunized with a peptide derived from nitrated α-synuclein into MPTPtreated mice results in an exacerbated neuronal loss in the SN (Benner et al 2008;Reynolds et al 2010).…”
Section: Associations Of Parkinson's Disease With Formation Of Neo-anmentioning
confidence: 96%
“…In this regard, nitrated α-synuclein is detected in cervical lymph nodes of mice when treated with MPTP, but not in healthy mice (Benner et al 2008). It is noteworthy that nitration of proteins not only enhances antigen presentation by human dendritic cells, but also promotes a strong activation and proliferation of specific Tcell clones (Karle et al 2012). Consistent with these findings, the adoptive transfer of T-cells obtained from mice immunized with a peptide derived from nitrated α-synuclein into MPTPtreated mice results in an exacerbated neuronal loss in the SN (Benner et al 2008;Reynolds et al 2010).…”
Section: Associations Of Parkinson's Disease With Formation Of Neo-anmentioning
confidence: 96%
“…Moreover, DEPs have the ability to stimulate OX40-L expression on DCs through induction of TSLP, similarly to allergens [75]. Other pollutants such as ozone and nitrogen dioxide may also disrupt epithelial junctions, enhance airway inflammation [34], facilitate the release of allergen granules, and induce nitration of common allergens such as Bet v 1 of birch pollen [76], which subsequently displays increased allergenic capacity.…”
Section: Air Pollutionmentioning
confidence: 99%
“…An additional hypothesized pollution effect is the induction of increased prevalence of allergies and asthma, through chemical alteration of the airborne allergens during their transport in the lower troposphere (Franze et al, 2005;Gruijthuijsen et al, 2006;Karle et al, 2012;Untersmayr et al, 2010), possibly by post-translational modifications (PTM). Previous studies have shown that Bet v 1.0101, an allergenic protein originated from birch pollen, undergoes nitration by mixtures of NO 2 and O 3 Gruijthuijsen et al, 2006;Walcher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%